Implementasi Kewajiban Kurator dalam Pembayaran Upah Pekerja Debitur Pailit: Analisis Putusan Mahkamah Agung Nomor 232 K/Pdt.Sus-Pailit/2021 - Marrietta, Donita Marsha; Adam, Richard C. (Universitas Ekasakti, 2023)
This research focuses on the construction of wrongful acts related to the duties of curators and the considerations of judges in Supreme Court decisions. The research aims to gain in-depth understanding of wrongful acts by curators and how judges consider such cases. The theoretical contribution of the research is expected to enhance the understanding of wrongful acts in curator actions. Practically, the research results are anticipated to offer new perspectives for legal researchers and practitioners, as well as guidance for those involved in bankruptcy cases, emphasizing the principles of justice, legal utility, and legal certainty. The research has the potential to enrich legal insights related to bankruptcy and support the improvement of legal policies and practices in facing bankruptcy challenges.